New Insights Into the Activity of Apple Dihydrochalcone Phloretin: Disturbance of Auxin Homeostasis as Physiological Basis of Phloretin Phytotoxic Action - Smailagić﻿﻿﻿, Dijana; Banjac, Nevena; Ninković﻿﻿﻿, Slavica; Savić﻿﻿﻿, Jelena; Ćosić﻿﻿﻿, Tatjana; Pěnčík, Aleš; Ćalić﻿﻿﻿, Dušica; Bogdanović﻿﻿﻿, Milica; Trajković﻿﻿﻿, Milena; Stanišić, Mariana (Frontiers in Plant Science, 2022)
Apple species are the unique naturally abundant source of dihydrochalcones, phenolic compounds with elusive role in planta but suggested auto-allelochemical features related to the ' apple replant disease' (ARD). Our aim was to elucidate the physiological basis of phytotoxic action of dihydrochalcone phloretin in model plant Arabidopsis and promote phloretin as a new prospective eco-friendly phytotoxic compound. Phloretin treatment induced a significant dose-dependent growth retardation and severe morphological abnormalities and agravitropic behavior in Arabidopsis seedlings. Histological examination revealed a reduced starch content of columella cells and serious disturbance in root architecture which resulted in reduced length of meristematic and elongation zones. Significantly disturbed auxin metabolome profile in roots with particularly increased content of IAA which accumulated in lateral parts of the root apex, accompanied with changes in expression of auxin biosynthetic and transport genes, especially PIN1, PIN3, PIN7 and ABCB1, indicated the role of auxin in physiological basis of phloretin-induced growth retardation. The results reveal a disturbance of auxin homeostasis as the main mechanism of phloretin phytotoxic action. This mechanism makes phloretin a prospective candidate for an eco-friendly bioherbicide and also paves the way for further research of phloretin role in ARD.